Adaptation in Translation: An Evaluation of the Nuptial Blessing in the 2018 Order of Celebrating Matrimony for the Roman Catholic Church in Nigeria - Usman, Victor Jamahh (2025)
This article seeks to interpret the implications and relevance of the Nuptial Blessing in the Order of Celebrating Matrimony within the context of Nigeria. The present prayer of the Nuptial Blessing as provided in the new order approved for the Roman Catholic Church in Nigeria (2018), missed capitalizing on the various provisions and possibilities for inculturation provided by the Ordo Celebrandi Matrimonium (OCM) of 1969 and 1991. In examining the history of the Nuptial Blessing, its basis in culture, its various adaptations and readaptations until the OCM of 1991, and some tenets of the Nigerian worldview concerning marriage blessings, this article posits that some elements of the Nuptial Blessing, which have been omitted over time, would have complemented the distinctive character and worldview of the Nigerian people, and that these features and even new ones could have been added in the new order approved for the Roman Catholic Church in Nigeria.
Keywords: Blessing; Order of Celebrating Matrimony; Vatican II; Nigerian worldview; Nigerian marriage; nuptial blessing; Liturgy; Marriage; Adaptation